2017
DOI: 10.1007/s00520-017-3841-2
|View full text |Cite
|
Sign up to set email alerts
|

Administration options for pegfilgrastim prophylaxis: patient and physician preferences from a cross-sectional survey

Abstract: Patients and physicians identified that returning clinic visits for pegfilgrastim administration may be burdensome. A potential solution to mitigate this burden is the OBI, which allows adherence to the labeled use of pegfilgrastim without return visits to the clinic.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
7
1
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 11 publications
5
7
1
2
Order By: Relevance
“…While age did not play a major role in patients' decision for either of the two application forms, the ECOG status at baseline had an influence, insofar as patients having an ECOG status of 0 had no clear preference, while for patients having an ECOG status of 1, the OBI seemed to be the better option, possibly as for this group of patients, return visits to the medical office might be particularly strenuous. This would be in line with findings of a cross-sectional survey on US patients' and physicians' preferences for pegfilgrastim application forms [20], in which physicians indicated to more likely prescribe the OBI when the patient's health was particularly compromised. At the same time, however, it was also suggested that especially for patients in a poor condition, an additional appointment at the medical office might be reasonable as it offers the opportunity to more closely monitor the patient's condition [20].…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…While age did not play a major role in patients' decision for either of the two application forms, the ECOG status at baseline had an influence, insofar as patients having an ECOG status of 0 had no clear preference, while for patients having an ECOG status of 1, the OBI seemed to be the better option, possibly as for this group of patients, return visits to the medical office might be particularly strenuous. This would be in line with findings of a cross-sectional survey on US patients' and physicians' preferences for pegfilgrastim application forms [20], in which physicians indicated to more likely prescribe the OBI when the patient's health was particularly compromised. At the same time, however, it was also suggested that especially for patients in a poor condition, an additional appointment at the medical office might be reasonable as it offers the opportunity to more closely monitor the patient's condition [20].…”
Section: Discussionsupporting
confidence: 82%
“…This would be in line with findings of a cross-sectional survey on US patients' and physicians' preferences for pegfilgrastim application forms [20], in which physicians indicated to more likely prescribe the OBI when the patient's health was particularly compromised. At the same time, however, it was also suggested that especially for patients in a poor condition, an additional appointment at the medical office might be reasonable as it offers the opportunity to more closely monitor the patient's condition [20]. The finding of the present study that higher proportions of both study nurses and physicians selected PS as the application form providing a better control over administration and side-effects might support this assumption and might have influenced their preference the most at the EOS, as a higher proportion of both study nurses and physicians indicated to prefer PS over OBI.…”
Section: Discussionsupporting
confidence: 82%
“…In the current study, an increase in use of pegfilgrastim OBI over the last 2 years was reported by two thirds of the oncologists, and they most commonly attributed this increase to convenient dosing and patients' need for an active lifestyle. These results reaffirm the findings from a 2016 survey of 200 patients and 200 oncologists, which found that avoiding the need to return to the clinic was the most important treatment feature in the opinion of both patients and oncologists [19].…”
Section: Tablesupporting
confidence: 82%
“…An on-body injector (OBI), approved in 2015 [18], can be applied on the same day as chemotherapy and automatically administers pegfilgrastim~27 h later, allowing patients to avoid a return visit. However, the perceptions and opinions of oncologists related to OBI use have not been studied since 2016, when a survey was conducted among early adopters [19].…”
Section: Introductionmentioning
confidence: 99%
“…Participants were identified and recruited through Survey Sampling International (SSI), a global panel provider and research partner for this study. SSI has access to panels of HCPs and patients who have agreed to participate in online research about health care-related issues and has recruited physicians and patients for published survey studies (e.g., [913]). SSI panel sources recruit HCPs from a variety of methods, including telephone or face-to-face via calling lists of hospitals and HCPs.…”
Section: Methodsmentioning
confidence: 99%